Gravitationally Consistent Mean Barystatic Sea Level Rise From Leakage‐Corrected Monthly GRACE Data. Issue 11 (19th November 2020) - Dobslaw, Henryk; Dill, Robert; Bagge, Meike; Klemann, Volker; Boergens, Eva; Thomas, Maik; Dahle, Christoph; Flechtner, Frank
Abstract: Gravitationally consistent solutions of the Sea Level Equation from leakage‐corrected monthly‐mean GFZ RL06 Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow‐On (GRACE‐FO) Stokes coefficients reveal that barystatic sea level averaged over the whole global ocean was rising by 1.72 mm a −1 during the period April 2002 until August 2016. This rate refers to a truely global ocean averaging domain that includes all polar and semienclosed seas. The result corresponds to 2.02 mm a −1 mean barystatic sea level rise in the open ocean with a 1, 000 km coastal buffer zone as obtained from a direct spatial integration of monthly GRACE data. The bias of +0.3 mm a −1 is caused by below‐average barystatic sea level rise in close proximity to coastal mass losses induced by the smaller gravitational attraction of the remaining continental ice and water masses. Alternative spherical harmonics solutions from CSR, JPL, and TU Graz reveal open‐ocean rates between 1.94 and 2.08 mm a −1, thereby demonstrating that systematic differences among the processing centers are much reduced in the latest release. We introduce in this paper a new method to approximate spatial leakage from the differences of two differently filtered global gravity fields. A globally constant and time‐invariant scale factor required to obtain full leakage from those filter differences is found to be 3.9 for GFZ RL06 when filtered with DDK3, and lies between 3.9 and 4.4 for other processing centers. Spatial leakage is estimated for every month in terms of global grids, thereby providing also valuable information of intrabasin leakage that is potentially relevant for hydrologic and hydrometeorological applications. Plain Language Summary: Satellite gravimetry as realized with the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow‐On (GRACE‐FO) missions is measuring tiny variations in the Earth's gravity field that are directly caused by divergent horizontal mass transports such as the melting of ice sheets and the corresponding discharge of melt water into the ocean basins. Between April 2002 and August 2016, this mass inflow caused sea level to rise by 1.72 mm each year as quantified from the latest GRACE reprocessing performed at our institute. The indirect observation principle of GRACE limits the spatial resolution so that highly localized mass loss signals are smeared out into the larger surrounding area, and possibly even from land into the ocean. We propose here a new method to quantify this so‐called spatial leakage from the difference of gravity fields smoothed with slightly different spatial filters. A scale factor is obtained from exploiting the availability of two independent methods to estimate the mass component of sea level rise: The first method spatially integrates over the global gravity fields in all regions away from the coasts, and the second method utilizes a (leakage‐corrected) mass distribution over the continents to calculate the gravitationally consistent distribution of water masses in all ocean basins. We estimate this scale factor as 3.9. Key Points: Mean barystatic sea level rise is biased high by 0.3 mm a −1 when estimated with a 1, 000 km coastal buffer zone Fractional spatial leakage in monthly GRACE gravity fields is quantified with two differently strong DDK filters Fractional leakage is scaled by a factor of 3.9 to make results from the Sea Level Equation consistent with open‐ocean integrations